The role of a community health worker-delivered preconception and pregnancy intervention in achieving a more positive pregnancy experience: the Bukhali trial in Soweto, South Africa - Larske M. Soepnel; Khuthala Mabetha; Shane A. Norris; Molebogeng Motlhatlhedi; Nokuthula Nkosi; Sonja Klingberg; Stephen Lye; Catherine E. Draper (BMC, 2024)
Abstract Background A patient-centered, human-rights based approach to maternal care moves past merely reducing maternal mortality and morbidity, towards achieving a positive pregnancy experience. When evaluating an intervention, particularly in the context of the complex challenges facing maternal care in South Africa, it is therefore important to understand how intervention components are experienced by women. We aimed to qualitatively explore (i) factors influencing the pregnancy and postpartum experience amongst young women in Soweto, South Africa, and (ii) the influence of Bukhali, a preconception, pregnancy, and early childhood intervention delivered by community health workers (CHWs), on these experiences. Methods Semi-structured, in-depth interviews were conducted with 15 purposively sampled participants. Participants were 18-28-year-old women who (i) were enrolled in the intervention arm of the Bukhali randomized controlled trial; (ii) were pregnant and delivered a child while being enrolled in the trial; and (iii) had at least one previous pregnancy prior to participation in the trial. Thematic analysis, informed by the positive pregnancy experiences framework and drawing on a codebook analysis approach, was used. Results The themes influencing participants' pregnancy experiences (aim 1) were participants' feelings about being pregnant, the responsibilities of motherhood, physical and mental health challenges, unstable social support and traumatic experiences, and the pressures of socioeconomic circumstances. In terms of how support, information, and care practices influenced these factors (aim 2), four themes were generated: acceptance and mother/child bonding, growing and adapting in their role as mothers, receiving tools for their health, and having ways to cope in difficult circumstances. These processes were found to be complementary and closely linked to participant context and needs. Conclusion Our findings suggest that, among women aged 18-28, a CHW-delivered intervention combining support, information, and care practices has the potential to positively influence women's pregnancy experience in South Africa. In particular, emotional support and relevant information were key to better meeting participant needs. These findings can help define critical elements of CHW roles in maternal care and highlight the importance of patient-centred solutions to challenges within antenatal care. Trial registration Pan African Clinical Trials Registry PACTR201903750173871, 27/03/2019.